(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
Historians of modern management link occurrence of this to the works of Taylor and Fayol and the birth of the great corporations of industrial capitalism, especially railways. The slave plantations have been deliberately omitted from this “dawn” of scientific management, however its coincidence and even priority in time and management methods, coupled with the clear separation between owners and managers give to those authentic character precursors scientific management. This paper attempts to show how the Cuban sugar mills in the second half of the nineteenth century are a clear example of rational and efficient management endorses it pointed in the paragraph above.